'The Alexandrian Condition': Suits on Boredom, Death, and Utopian Games. Issue 3 (2nd October 2019) - Yorke, Christopher C.
ABSTRACT: I argue that the apparently exclusive choice between Suits' utopia of gameplay and death by suicide is a false dilemma, one which obscures a 'third way' of positive boredom. Further, I offer a deeper reading of the internal logic of Suits' utopian vision, identifying two different temporal phases of his utopia. At time U1, just after the founding of Suits' techno-Cockaygne, the Alexandrian condition affects 'freshmen' utopians by producing a state of existential meaninglessness and thereby conceivably motivating utopian suicide. At time U2, however, sufficient time will have passed for the surviving 'sophomore' utopians to adopt marvelous, meaning-generative utopian games as a tool for defeating the Alexandrian condition and thus realizing Suits 'ideal of existence' in a utopia of gameplay.